Cytoplasmic Connexin32 and Self-Renewal of Cancer Stem Cells: Implication in Metastasis - Omori, Yasufumi; Kawasaki, Yohei; Li, Qingchang; Yoshioka, Toshiaki; Yamamoto, Yohei; Enomoto, Katsuhiko (IntechOpen, 2012)
None